Identification of a Novel Inhibitor of TfR1 from Designed and Synthesized Muriceidine A Derivatives - Yu Wu; Zongchen Ma; Xiaoyuan Mai; Xiaoling Liu; Pinglin Li; Xin Qi; Guoqiang Li; Jing Li (MDPI AG, 2022)
The transferrin receptor 1 (TfR1) plays a key role in cellular iron uptake through its interaction with iron-bound Tf. TfR1 is often reported to be overexpressed in malignant cells, and this increase may be associated with poor prognosis in different types of cancer, which makes it an attractive target for antitumor therapy. The marine natural product Muriceidine A is a potent anticancer agent reported in our previous work. In this study, we designed and synthesized a series of Muriceidine A derivatives and described the systematic investigation into their cytotoxic activities against four tumor cells. Most of the derivatives showed stronger antitumor activity and we found that the introduction of electron-donating groups at position C-2 of unsaturated piperidine was beneficial to anticancer activity and unsaturated piperidine was responsible for the antiproliferative activity. Among these compounds, 12b (methyl at position C-2 of unsaturated piperidine) exhibited the strongest cytotoxicity against MDA-MB-231 cells. Further pharmacological research showed that 12b bound to Transferrin receptor 1 (TfR1) directly caused iron deprivation and ROS imbalance along with the degradations of several oncoproteins, especially FGFR1, through the proteasome pathway; thus, inducing cell cycle arrest and apoptosis in MDA-MB-231 breast cancer cells. Our findings indicate that 12b is a promising lead compound targeting TfR1 for triple negative breast cancer.